Exploring the Antecedents of New Knowledge Creation in Organizational Settings: An Empirical Study - MENKHOFF, Thomas (Institutional Knowledge at Singapore Management University, 2010)
This study aims to understand the antecedents of new knowledge creation in knowledge-intensive organizations. A model of knowledge management and new knowledge creation inspired by the works of Nonaka, Nahapiet and Ghoshal and others was used to develop a questionnaire. 213 individuals responded from a knowledge-based organization in Singapore. The results of the study indicated that knowledge tools and technologies interact with the modus of knowledge combination to influence knowledge outcomes in terms of worker skills, competencies, market knowledge and client relationships. The key ingredients for creating new knowledge as well as synergistic collaborations between various knowledge players are also discussed.